Design Band Stop Filter Untuk Jaringan WiMAX 3.5 GHz - S, Linna Oktaviana; Hidayat, Fauzi; Safrianti, Ery (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Along with the development of technology-based Broadband Wireless Access (BWA), it is not just a connection is needed, but also the speed of the internet access and large capacity. One of the technology in BWA currently used is IEEE 802.16d WiMAX standard. IEEE 802.16d WiMAX standard using a frequency of 3.5 GHz. Indonesian satellite using the same frequency with the frequency of WiMAX. In order to avoid any interference between WiMAX and satellite it is necessary to filter on the WiMAX receiver. Therefore bandstop filter is used to reject the frequency of satellite based WiMAX standard has been set. In this thesis report discusses the design of bandstop filter circuit consisting of components - namely passive components, inductors and capacitors. Responses were used in this design is the Chebyshev response for Chebyshev response can result in a high degree of steepness of the passband to stopband. Software used in the design of band-stop filter is the Advanced Design System (ADS) 2011. Keywords : FM Modulator, Modulated Signal, Phase Locked Loop, Carrier Signal,          Information Signal.